Analisis Perilaku Kecurangan (Fraud) Tenaga Kerja UMKM terhadap Keberlangsungan Usaha: Studi Kasus pada UMKM HJ.GUS BUSANA - Hafizh Dzaky Hawari; Rizki Aryanto; Abda Abda; Rifqi Muzakki (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting national economic growth, particularly through their contributions to job creation and the development of local potential. MSMEs serve as the backbone of inclusive economic development by reaching various segments of society. However, despite their strategic importance, MSMEs often face internal challenges, including the risk of fraud committed by employees. This study aims to examine the forms of fraud risk occurring within the MSME HJ.GUS BUSANA and analyze their impact on business operations. A qualitative descriptive approach was used, with data collected through direct interviews with the business owner. This method allowed for a contextual and in-depth understanding of the types of fraud experienced. The findings reveal two primary forms of employee fraud that pose a threat to operational efficiency and business sustainability. First, the excessive use of raw materials without the owner’s knowledge or approval, categorized as a high-risk behavior. Second, the use of business facilities such as equipment and working hours for personal purposes, categorized as a moderate-risk behavior. These practices lead to resource wastage, increased operational costs, and decreased productivity. The impact of such fraud is not only financial but can also erode trust within the workplace environment. Therefore, a more effective internal control system is essential, including proper monitoring of material usage and access to business resources. Additionally, instilling strong work ethics and a sense of responsibility among employees is crucial in building a positive organizational culture. Implementing these measures is key to ensuring that MSMEs can not only survive but also grow sustainably amidst the ever-changing business landscape. Strengthening internal supervision and ethical awareness can significantly reduce the risk of fraud, thereby enhancing the long-term resilience and performance of the enterprise.